2022
DOI: 10.3389/fcimb.2022.1044984
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of Psittacosis cases in Lishui, Zhejiang Province, China, in 2021

Abstract: IntroductionPsittacosis, caused by Chlamydia psittaci, is widespread throughout the world. In humans, C. psittaci infection may lead to severe conditions and complications, including sepsis and multiple organ failure. We report a cluster of cases caused by C. psittaci in Zhejiang Province, 2021, which led to one death and three cases of hospitalization.MethodsThe cases were confirmed by nest-PCR, RT-PCR, and mNGS.ResultsThe four cases were related and the sequences obtained from the samples were closely correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…reported, C. psittaci -positive cases were closely associated with older persons (≥30 years) who had respiratory signs and handled birds in pet markets ( Tolba et al., 2019 ). In a cluster of psittacosis cases in Zhejiang Province of China, the patients range from 42-70 years old ( Yao et al., 2022 ). Nevertheless, we are reporting a highly suspected younger case of C. psittaci -infection (case 1, five years old), which is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…reported, C. psittaci -positive cases were closely associated with older persons (≥30 years) who had respiratory signs and handled birds in pet markets ( Tolba et al., 2019 ). In a cluster of psittacosis cases in Zhejiang Province of China, the patients range from 42-70 years old ( Yao et al., 2022 ). Nevertheless, we are reporting a highly suspected younger case of C. psittaci -infection (case 1, five years old), which is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers collected 74 samples, including throat swabs, anal swabs, and poultry drinking water. Of these samples, 8 were positive ( Yao et al., 2022 ). Therefore, the diagnosis of psittacosis was confirmed in all four cases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cases 1 and 2 underwent blood mNGS testing, which demonstrated a higher number of mNGS sequences in the alveolar lavage fluid compared to peripheral blood ( Table 3 ). Phylogenetic analysis of genes in a study on disease control in Lishui City indicated that 11 sequences from four cases were closely related and clustered together on the same branch, indicating high homology ( Yao et al., 2022 ).…”
Section: Pathogenic Examinationmentioning
confidence: 99%
“…Lishui is located in the southwest of Zhejiang Province, China (118 • 41 -120 • 26 E, 27 • 25 -28 • 57 N), with a total area of 17,298 km 2 [37] (Figure 1). Lishui is a prefecturelevel city with the largest land area in Zhejiang Province.…”
Section: Study Areamentioning
confidence: 99%